The Effect of STEAM-Based Hybrid Based Learning Model on Students' Critical Thinking Skills - Wasito Utomo; Wiwid Suryono; Jimmi Jimmi; Tomi Apra Santosa; Ika Agustina (Jurnal Penelitian Pendidikan IPA, 2023)
The purpose of the study was to determine the effect of STEAM-based hybrid based learning model on students' critical thinking skills. This research is a type of meta-analysis research. The research data came from 15 national and international journals. The process of searching for data sources through the google scholar database, Science Direct, Eric, Plos ONE and Wiley. The data selection method is the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method. The inclusion criteria for this meta-analysis research are that the research must be published in the last 5 years 2018-2023, the research must use experimental or quasi-experimental methods, the research must have an experimental class that applies a hybrid-based learning model and a control class, the research comes from journals indexed by SINTA and Scopus, and the research has complete data to calculate the effect size. The data analysis technique is quantitative analysis by calculating the effect size value, research heterogeneity and publication bias with the help of the Comprehensive Meta-analysis (CMA) version.3 application. The results of the study concluded that the summary effect size or average effect size (p < 0.01; ES = 1.052) criteria were strong. This finding explains that the hybrid-based learning model has a significant effect on students' critical thinking skills. This STEAM-based hybrid-based learning model has a higher effect on students' critical thinking skills than the conventional model. Model has a high influence on students' critical thinking skills than conventional models